2013
DOI: 10.1002/stem.1268
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Self-Organizing Neuroepithelium from Human Pluripotent Stem Cells Facilitates Derivation of Photoreceptors

Abstract: Retinitis pigmentosa, other inherited retinal diseases, and age-related macular degeneration lead to untreatable blindness because of the loss of photoreceptors. We have recently shown that transplantation of mouse photoreceptors can result in improved vision. It is therefore timely to develop protocols for efficient derivation of photoreceptors from human pluripotent stem (hPS) cells. Current methods for photoreceptor derivation from hPS cells require long periods of culture and are rather inefficient. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 41 publications
(62 reference statements)
3
63
0
Order By: Relevance
“…In terms of timing, differentiation of NR-like structures is quite similar to the ones reported for the in vitro self-formed OC and OV-like structures (16,17), with the detection of RGCs between D21 and D35 and photoreceptor precursors around D30-D40 whereas more mature photoreceptors, stained for the presence of OPSIN or RHODOPSIN, were not clearly identified before D77. The use of different molecules during the culture, such as taurine, sonic hedgehog, retinoic acid, FGF1, and FGF2, could accelerate photoreceptor maturation, as recently reported for hESC aggregates in the presence of Matrigel (28). Interestingly, we report that inhibition of the Notch pathway when RPCs are committed to the photoreceptor lineage clearly enhances the proportion of photoreceptor precursors in the NR-like structures, with a twofold increase in CRX + cells, presumably achieved by forcing RPCs to exit early from the cell cycle, as previously described (16).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In terms of timing, differentiation of NR-like structures is quite similar to the ones reported for the in vitro self-formed OC and OV-like structures (16,17), with the detection of RGCs between D21 and D35 and photoreceptor precursors around D30-D40 whereas more mature photoreceptors, stained for the presence of OPSIN or RHODOPSIN, were not clearly identified before D77. The use of different molecules during the culture, such as taurine, sonic hedgehog, retinoic acid, FGF1, and FGF2, could accelerate photoreceptor maturation, as recently reported for hESC aggregates in the presence of Matrigel (28). Interestingly, we report that inhibition of the Notch pathway when RPCs are committed to the photoreceptor lineage clearly enhances the proportion of photoreceptor precursors in the NR-like structures, with a twofold increase in CRX + cells, presumably achieved by forcing RPCs to exit early from the cell cycle, as previously described (16).…”
Section: Discussionsupporting
confidence: 59%
“…Early generated structures present an OV phenotype revealed by coexpression of PAX6 and RAX, and an opposite gradient of VSX2 and MITF between the neuroepithelium and the RPE. This efficiency is likely due in part to the increasing endogenous production by confluent hiPSCs of DKK1 and NOG-GIN, two inducers of neural and retinal specification, generally added for retinal differentiation of hESCS or hiPSCs (17,28).…”
Section: Discussionmentioning
confidence: 99%
“…23,33,36,37 Thus, one of the important tasks of transplanted hESC-RPE is to produce sufficient ECM to restore the functions of the damaged BM if no BM mimicking nonbiodegradable biomaterial is used with cells. 16,17 Previously, it has been shown that ECM affects the early stage differentiation of hPSCs into neural progenitors and neurons, 38 retinal progenitor cells, 39,40 and RPE cells. 41 In addition, different ECM proteins have been used in differentiation of hESC-RPE.…”
Section: Introductionmentioning
confidence: 99%
“…30 To avoid the presence of animal derivatives (animal-derived sera, or in most cases Matrigel), a chemically defined 3D retinal differentiation medium was recently reported, which only contains nicotinamide and 20 ng/mL of basic fibroblast growth factor. 121 To date, efforts to speed up the differentiation protocols 31,122,123 using molecules known to promote retinal differentiation 31,118,123 or by passing the EB formation 122 have generally reduced the survival of differentiated cells, 31,123 and/or the stratification obtained. 122 Whether correct lamination of pluripotent stem cell-derived donor retinal tissue is required for generation of transplantationcompetent human photoreceptor cells remains to be resolved.…”
Section: Simplicity and Speedmentioning
confidence: 99%